Milczaca godnosc - Steel, Danielle; Bukojemska, Izabela (Warszawa : Wydawn. Amber, 2000)
Polish translation of "Silent Honor". The year 1941--a young Japanese woman arrives in California for higher studies. She is just beginning to get used to American life when the war breaks out, which cuts her off from her lover.
Translation of: Silent honor.
Keywords: Japanese Americans -- Evacuation and relocation,1942-1945 -- Fiction; Japanese Americans -- California -- Fiction; Young women -- California -- Fiction